Tissue adhesion material as well as preparation method and application thereof

By using multi-copolymer tissue adhesion materials prepared in combination with itaconic acid and other compounds, the problems in the prior art that itaconic acid is difficult to simultaneously meet high adhesion, mechanical strength, degradability and prevention of postoperative adhesion are achieved, and efficient and safe tissue adhesion and hemostasis effects are achieved.

CN119857169APending Publication Date: 2025-04-22SURGSCI SHENZHEN MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077928.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to meet the needs of high adhesion, mechanical strength, degradability and postoperative adhesion prevention when designing tissue adhesion materials, and the source of the material is at risk of infectious diseases.

Method used

Itaconic acid is used as the reaction monomer to prepare a multivariate copolymer tissue adhesion material by combining itaconic acid, film-forming compound, initiator and promoter. The material is obtained by heat-induced radical polymerization and esterification, which has stable adhesion and mechanical strength, and is degradable, reducing the risk of postoperative adhesion.

Benefits of technology

The high adhesion, mechanical strength and degradability of tissue adhesive materials are achieved, which reduces the risk of shedding during service, and avoids postoperative adhesions, and has good biocompatibility and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857169A_ABST
    Figure CN119857169A_ABST
Patent Text Reader

Abstract

The invention relates to a tissue adhesion material and a preparation method and application thereof, the tissue adhesion material comprises a linear-chain or branched-chain ternary or more multipolymer, and the multipolymer is prepared from itaconic acid, a tissue adhesion compound, a film-forming compound, an initiator and an accelerant. The tissue adhesion material provided by the invention has stable tissue adhesion performance, can effectively adhere damaged tissues, provides certain mechanical support and protection, achieves a hemostatic effect, is low in swelling property, reduces the risk of falling off during service, and is excellent in comprehensive performance and good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a tissue adhesion material and a preparation method and application thereof. Background Art

[0002] Every year, millions of people suffer physical injuries, including accidental injuries, surgical procedures, chronic ulcers, and in severe cases, life-threatening injuries. Currently, the commonly used mechanical means in clinical practice are sutures or staples, which are prone to stress concentration in wounds, remain in the body for a long time, and may leak air or fluid. Adhesives are used as an improved means, such as cyanoacrylate or fibrin adhesives to adhere and close wounds, and are used to stop bleeding or assist in stopping bleeding. However, cyanoacrylate is cytotoxic, and high bonding strength can easily lead to adhesion. Fibrin hemostatic glue has high hemostatic performance and biocompatibility, but poor adhesion and mechanical properties, and the source of the material has the risk of infectious diseases. Tissue adhesive films are gradually being valued for their convenient operation, high wound closure efficiency without secondary damage, and are expected to replace sutures in the application of surgical wound closure.

[0003] More and more people realize that in addition to meeting basic safety requirements, adhesive materials should also have mechanical strength that conforms to tissues and adhesion properties to traumatic areas. Tissue patches should be flexible enough to fit tightly with tissues and prevent liquid / gas from leaking from adhesive gaps. Strong flexibility is conducive to enriching the application scenarios of patch materials, such as being used in minimally invasive surgery through catheters. When designing adhesive materials, stable adhesion and cohesive energy should be ensured, that is, the material should form a strong interface bond with the tissue part, while providing the required cohesive strength and maintaining stability to obtain the required support during wound recovery. The adhesion process of tissue patches when contacting tissues is to interact through hydrogen bonds within 3-5 seconds, hydrate with water at the tissue interface to obtain initial adhesion, and form covalent bonds such as amide bonds, ester bonds, disulfide bonds, etc. with amine, hydroxyl or thiol groups in the tissue at 60 seconds to obtain stronger and more lasting adhesion; tissue patches should be degradable to prevent patients from suffering secondary injuries. In order to obtain high adhesion, the existing technology usually uses catechol as the adhesive functional group in the design, but this group is easily oxidized, the film appearance is opaque, and it is not conducive to the immediate observation of wound hemostasis. The ideal adhesive material should have basic characteristics such as biocompatibility, degradability, prevention of postoperative adhesion, easy preparation, and easy use.

[0004] Therefore, it is necessary to provide a tissue adhesion material with stable and excellent tissue adhesion properties, which can effectively adhere to damaged tissues, provide certain mechanical support and protection, and achieve hemostasis. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a tissue adhesion material and a preparation method and application thereof. The tissue adhesion material provided by the present invention has stable tissue adhesion performance, can effectively adhere to damaged tissue, provide certain mechanical support and protection, achieve hemostasis, and has low swelling, reducing the risk of falling off during service, excellent comprehensive performance, and good application prospects.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a tissue adhesion material, which includes a linear or branched ternary or higher copolymer, and the raw materials for preparing the copolymer include itaconic acid, a tissue adhesion compound, a film-forming compound, an initiator and a promoter.

[0008] The present invention uses itaconic acid as a reactive monomer to prepare a tissue adhesion material for the first time. Itaconic acid contains two active carboxyl groups, which are convenient for grafting tissue adhesion groups, regulating the effects of covalent bonds and non-covalent bonds, and can effectively improve adhesion. At the same time, the water absorption is low, and the adhesion strength, mechanical strength, and degradation time of the obtained tissue patch are controllable. At the same time, the swelling is low, which reduces the risk of falling off during service. The raw materials for preparing the tissue adhesion material provided by the present invention are cheap, simple and easy to obtain, and itaconic acid also has antibacterial, anti-inflammatory, antioxidant and antiviral functions, and has a high cost performance.

[0009] Preferably, the tissue adhesive compound comprises any one of imidate, N-hydroxysuccinimide, acrylate, maleimide, glutaraldehyde, catechol, epoxide, isocyanate or vinyl compound, or a combination of at least two thereof.

[0010] The vinyl compound described in the present invention may be, for example, vinyl sulfone.

[0011] Tissue adhesive compounds contain functional groups that can react with groups (such as thiols, primary amines, etc.) on the tissue surface to form covalent bonds, which can provide long-term adhesion. The adhesion properties of tissue adhesive materials can be improved by introducing the above-mentioned tissue adhesive compounds.

[0012] Preferably, the molar ratio of itaconic acid to the tissue adhesive compound is 5:1-1:5 (for example, it can be 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, etc.).

[0013] Preferably, the film-forming compound includes any one of N-vinyl pyrrolidone, styrene, methyl methacrylate or butyl acrylate, or a combination of at least two thereof.

[0014] Preferably, the molar ratio of itaconic acid to the film-forming compound is 5:1-1:5 (for example, it can be 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, etc.).

[0015] Preferably, the initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, persulfate or dibenzoyl peroxide, or a combination of at least two thereof.

[0016] Preferably, the accelerator includes any one of N,N-dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride or a combination of at least two thereof.

[0017] Preferably, the raw materials for preparing the multi-polymer further include a cross-linking agent.

[0018] In the present invention, in a preferred embodiment, a cross-linking agent is introduced to connect itaconic acid and a film-forming compound to form a polymer main chain, thereby fully satisfying the flexibility of the film.

[0019] Preferably, the cross-linking agent includes any one of polyethylene glycol diacrylate, polypropylene glycol diacrylate, polycaprolactone, polyurethane or polyacrylamide, or a combination of at least two thereof.

[0020] Preferably, the molar ratio of itaconic acid to the cross-linking agent is 1:1-50:1 (for example, it can be 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, etc.).

[0021] In a second aspect, the present invention provides a method for preparing the tissue adhesion material according to the first aspect, the preparation method comprising the following steps:

[0022] (1) mixing an itaconic acid monomer, an initiator and a solvent, and subjecting the mixture to a free radical polymerization reaction initiated by heat to obtain a solution A;

[0023] (2) mixing solution A, a film-forming compound and an initiator, and subjecting the mixture to a free radical polymerization reaction initiated by heat to obtain solution B;

[0024] (3) Solution B, the tissue adhesion compound and the accelerator are mixed and subjected to an esterification reaction to obtain the tissue adhesion material.

[0025] In the present invention, the tissue adhesion material is obtained by heat-induced free radical polymerization and esterification reaction. Compared with light-induced free radical polymerization, the structure and molecular weight of the product obtained by heat-induced free radical polymerization are relatively controllable and have good repeatability.

[0026] Preferably, the amount of the initiator in step (1) is 0.2-5% (for example, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.) of the total mass of itaconic acid and the cross-linking agent.

[0027] Preferably, the solvent in step (1) comprises any one of dimethyl sulfoxide, deoxygenated toluene, N,N-dimethylformamide, 1,4-dioxane or N,N-dimethylacetamide, or a combination of at least two thereof.

[0028] Preferably, the amount of the solvent used in step (1) is 2-10 times (for example, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, etc.) the total mass of itaconic acid and the cross-linking agent.

[0029] Preferably, the temperature of the free radical polymerization reaction in step (1) is 40-80°C (for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.), and the time of the free radical polymerization reaction is 1-24h (for example, it can be 1h, 4h, 8h, 12h, 16h, 20h, 24h, etc.).

[0030] Preferably, step (1) further comprises adding a cross-linking agent and mixing it with the itaconic acid monomer, the initiator and the solvent.

[0031] Preferably, the amount of the initiator in step (2) is 0.2-2% of the mass of the film-forming compound (for example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.).

[0032] Preferably, the temperature of the free radical polymerization reaction in step (2) is 40-80°C (for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.), and the time of the free radical polymerization reaction is 1-24h (for example, it can be 1h, 4h, 8h, 12h, 16h, 20h, 24h, etc.).

[0033] Preferably, the molar ratio of the tissue adhesion compound to the promoter in step (3) is 1:0.5-1:2 (for example, it can be 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, etc.).

[0034] Preferably, the temperature of the esterification reaction in step (3) is 20-30°C (for example, it can be 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, etc.), and the time of the esterification reaction is 24-96h (for example, it can be 24h, 32h, 40h, 48h, 56h, 64h, 72h, 80h, 88h, 96h, etc.).

[0035] Preferably, the esterification reaction in step (3) further includes a post-treatment step.

[0036] Preferably, the post-treatment comprises filtering the system after the esterification reaction, adding a precipitant to the filtrate for precipitation, then redissolving the precipitate, and adding the precipitant again for precipitation; then washing the precipitate with a detergent to obtain the tissue adhesion material.

[0037] Preferably, the precipitant comprises any one of ethanol, isopropanol, n-propanol, diethyl ether or ethyl acetate, or a combination of at least two thereof.

[0038] Preferably, the solvent used for the re-dissolution includes any one of dichloromethane, chloroform or methanol, or a combination of at least two of them.

[0039] Preferably, the detergent comprises any one of ether, n-hexane, petroleum ether, ethyl acetate, butyl benzoate, carbon tetrachloride, propyl ether or n-pentane, or a combination of at least two thereof.

[0040] In the present invention, the "room temperature" is 15°C-25°C, for example, it can be 15°C, 18°C, 20°C, 22°C, 25°C, etc.

[0041] In a third aspect, the present invention provides a use of the tissue adhesion material according to the first aspect in the preparation of a hemostatic agent, a tissue sealant, a wound adhesive or a drug carrier.

[0042] In a fourth aspect, the present invention provides a tissue patch, the tissue patch comprising a stacked tissue adhesion layer and an anti-tissue adhesion layer;

[0043] The tissue adhesion layer comprises the tissue adhesion material according to the first aspect.

[0044] The tissue patch provided by the present invention can achieve rapid adhesion to tissues, has stable mechanical properties, and is biodegradable. Its tissue adhesion layer has stable and excellent tissue adhesion properties, can effectively adhere to damaged tissues, provide certain mechanical support and protection, and achieve a hemostatic effect; the smooth anti-tissue adhesion layer can hinder the adhesion of proteins and fibroblasts, etc., to avoid postoperative tissue adhesion.

[0045] The tissue patch of the present invention is prepared by a film-casting method, and has a uniform and transparent form, excellent mechanical and adhesive properties, and has the advantages of being degradable and having low swelling properties.

[0046] Preferably, the anti-tissue adhesion layer comprises any one of polylactic acid, polyglycolic acid, polycaprolactone, polyhydroxyalkanoate or lactic acid-glycolic acid copolymer, or a combination of at least two thereof.

[0047] The anti-tissue adhesion layer provided by the present invention has film-forming property, non-toxicity, biocompatibility and biodegradability, and can effectively prevent the occurrence of postoperative adhesion.

[0048] Preferably, the thickness of the tissue patch is 0.01-1 mm (for example, it may be 0.01 mm, 0.02 mm, 0.05 mm, 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, etc.).

[0049] Compared with the prior art, the present invention has at least the following beneficial effects:

[0050] (1) The present invention uses itaconic acid as a reaction monomer to synthesize a tissue adhesion layer, making full use of the active carboxyl group in itaconic acid to meet high adhesion. The raw materials for preparing the tissue adhesion layer are simple, cheap and easy to obtain, and itaconic acid also has antibacterial, anti-inflammatory, antioxidant and antiviral functions, and is cost-effective. In the preferred embodiment of the present invention, a cross-linking agent is introduced to connect itaconic acid and a film-forming compound to form a polymer main chain, which can also fully meet the flexibility of the film and further improve the performance of the tissue adhesion layer.

[0051] (2) The tissue patch provided by the present invention has adjustable adhesion strength, mechanical strength, and degradation time; low swelling, which can reduce the risk of falling off during service; high toughness, strong compliance when adhering to tissue, and not easy to rupture; biodegradable, no need for secondary surgery to remove, and will not cause secondary damage to the tissue; good hemostatic properties, after contacting the wound, it forms a blood clot with body fluids to achieve the effect of hemostasis. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is the infrared spectra of IA, the copolymer P(NVP-co-IA-co-IA(NHS)) provided in Example 1, and the copolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS)) provided in Example 2.

[0053] Figure 2 This is a diagram of the adhesion mechanism of the tissue patch in Application Example 1.

[0054] Figure 3 It is the in vitro degradation diagram of the products provided in Application Example 2 and Comparative Application Example 1. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0056] The following abbreviations are used in the following examples:

[0057] AIBN: Azobisisobutyronitrile

[0058] DCC: dicyclohexylcarbodiimide

[0059] DMF: N,N-dimethylformamide

[0060] DMF: Dimethyl sulfoxide

[0061] DCM: dichloromethane

[0062] IA: itaconic acid

[0063] AA: Acrylic acid

[0064] D,L-DA: D,L-dopamine

[0065] MEOH: Methanol

[0066] NVP: N-vinyl pyrrolidone

[0067] NHS: N-hydroxysuccinimide

[0068] PEGDA: Polyethylene glycol diacrylate

[0069] PLGA: D,L-lactide-glycolide copolymer

[0070] Mn: number average molecular weight

[0071] Mw: weight average molecular weight

[0072] Example 1

[0073] Preparation of P(NVP-co-IA-co-IA(NHS))[N-vinylpyrrolidone, itaconic acid and itaconic acid NHS ester] terpolymer

[0074] The structure and preparation route of P(NVP-co-IA-co-IA(NHS)) are shown below:

[0075]

[0076] Where x+y≤m;

[0077] 11.114 g (0.1 mol) of NVP and 13.01 g (0.1 mol) of IA were weighed and added to a four-necked flask containing 120 mL of DMSO, and mechanical stirring was started until they were completely dissolved; 0.048 g of AIBN was weighed and added to the reaction system, and the reaction was carried out at 60 ° C for 10 h under a nitrogen environment; after the reaction was stopped, the reaction system was naturally cooled to room temperature, 11.509 g (0.1 mol) of NHS and 20.633 g (0.1 mol) of DCC were weighed and dissolved in 160 mL of DMSO and added to the reaction system, and magnetic stirring was carried out at 25 ° C for 96 h; after the reaction was completed, the reaction by-product DCU was removed by filtration, and the solution was precipitated in 2000 mL of anhydrous ethanol and filtered to obtain a solid product, the solid product was washed three times with 1000 mL of ether, and then dried at 40 ° C under reduced pressure to obtain P (NVP-co-IA-co-IA (NHS)).

[0078] The molecular weight is approximately Mn=1000-100000, Mw=1000-100000.

[0079] Example 2

[0080] Preparation of tetrapolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS))[N-vinylpyrrolidone, polyethylene glycol diacrylate, itaconic acid and itaconic acid NHS ester]

[0081] The synthetic route of P(NVP-co-PEGDA-co-IA-co-IA(NHS)) is as follows:

[0082]

[0083] The possible structure of P(NVP-co-PEGDA-co-IA-co-IA(NHS)) is shown below:

[0084]

[0085] Weigh 0.066 g AIBN and dissolve it in 120 mL DMSO. After it is completely dissolved, add 13.01 g (0.1 mol) IA and 20 g (0.05 mol) PEGDA (Mn = 400). Start mechanical stirring until the solution is fully mixed. React at 60 ° C for 24 h under nitrogen environment. Then weigh 11.114 g (0.1 mol) NVP and 0.0222 g AIBN and add them to the reaction system and continue to react at 60 ° C for 24 h.

[0086] The reaction system was naturally cooled to room temperature, 11.509 g (0.1 mol) of NHS and 20.633 g (0.1 mol) of DCC were weighed and dissolved in 100 mL of DMSO, and then added to the above-obtained polymer solution, and reacted at 25°C for 96 hours to obtain a viscous liquid; after the reaction, the reaction by-product DCU was removed by filtration, and the solution was precipitated in 2000 mL of isopropanol and filtered to obtain a solid product, which was washed three times with 1000 mL of ethyl acetate and then dried at 40°C under reduced pressure.

[0087] The molecular weight is approximately Mn=5000-100000, Mw=5000-100000.

[0088] The infrared spectra of the copolymer P(NVP-co-IA-co-IA(NHS)) provided in Example 1 and the copolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS)) provided in Example 2 are as shown in FIG. Figure 1 shown.

[0089] Example 3

[0090] Preparation of tetrapolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS))[N-vinylpyrrolidone, polyethylene glycol diacrylate, itaconic acid and itaconic acid NHS ester]

[0091] Weigh 0.066 g AIBN and dissolve it in 120 mL deoxygenated toluene. After it is completely dissolved, add 13.01 g (0.1 mol) IA and 14 g (0.02 mol) PEGDA (Mn = 700). Start mechanical stirring until the solution is fully mixed. React at 60 ° C for 24 h under nitrogen environment. Then weigh 11.114 g (0.1 mol) NVP and 0.044 g AIBN and add them to the reaction system and continue to react at 60 ° C for 24 h.

[0092] The reaction system was naturally cooled to room temperature, 11.509 g (0.1 mol) of NHS and 20.633 g (0.1 mol) of DCC were weighed and dissolved in 100 mL of deoxygenated toluene, and then added to the above-obtained polymer solution, and reacted at 25°C for 96 hours to obtain a viscous liquid; after the reaction, the reaction by-product DCU was removed by suction filtration, and the solution was precipitated in 1500 mL of ether and filtered to obtain a solid product, which was washed three times with 1000 mL of acetone and then dried at 40°C under reduced pressure.

[0093] The molecular weight is approximately Mn=5000-100000, Mw=5000-100000.

[0094] Example 4

[0095] Preparation of tetrapolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS))[N-vinylpyrrolidone, polyethylene glycol diacrylate, itaconic acid and itaconic acid NHS ester]

[0096] Weigh 0.066g AIBN and dissolve it in 120mL DMF. After it is completely dissolved, add 13.01g (0.1mol) IA and 20g (0.02mol) PEGDA (Mn = 1000), start mechanical stirring until the solution is fully mixed, react at 60°C for 24h under nitrogen environment, weigh 11.114g (0.1mol) NVP and 0.088g AIBN and add them to the reaction system and continue to react at 60°C for 24h. Let the reaction system stand at room temperature, dialyze and freeze-dry for three days to obtain pure P (NVP-PEGDA-IA);

[0097] Weigh 20 g of P(NVP-PEGDA-IA) and dissolve it in 100 mL of DMSO. Stir until the copolymer is completely dissolved. Under a nitrogen environment, add 46.036 g (0.4 mol) of NHS and 82.532 g (0.04 mol) of DCC dissolved in DMSO and react at 25 °C for 96 h. After the reaction, filter and precipitate the filtrate in acetone three times to obtain a white product, which is then dried in vacuum for 3 days.

[0098] The molecular weight is approximately Mn=5000-100000, Mw=5000-100000.

[0099] Example 5

[0100] Preparation of P(NVP-co-PEGDA-co-IA-co-IA-DA)[N-vinylpyrrolidone, polyethylene glycol diacrylate, itaconic acid and itaconic acid dopamine] tetrapolymer

[0101] Weigh 0.066 g AIBN and dissolve it in 120 mL DMSO. After it is completely dissolved, add 13.01 g (0.1 mol) IA and 20 g (0.05 mol) PEGDA (Mn = 400). Start mechanical stirring until the solution is fully mixed. React at 60 ° C for 24 h under nitrogen environment. Then weigh 11.114 g (0.1 mol) NVP and 0.222 g AIBN and add them to the reaction system and continue to react at 60 ° C for 24 h.

[0102] The reaction system was naturally cooled to room temperature, 18.964 g (0.1 mol) of D,L-dopamine (D,L-DA), 11.509 g of NHS (0.1 mol) and 20.633 g (0.1 mol) of DCC were weighed and dissolved in 100 mL of DMF, and then added to the above-obtained polymer solution, and reacted at 25°C for 96 hours to obtain a viscous liquid; after the reaction, the reaction by-product DCU was removed by filtration, and the solution was precipitated in 2000 mL of isopropanol and filtered to obtain a solid product, which was washed three times with 1000 mL of ethyl acetate and then dried at 40°C under reduced pressure.

[0103] The molecular weight is approximately Mn=5000-100000, Mw=5000-100000.

[0104] Comparative Example 1

[0105] Preparation of P(NVP-co-AA-co-AA(NHS))[N-vinylpyrrolidone, acrylic acid and NHS acrylate] terpolymer

[0106] 121.3g (1.09mol) NVP and 78.7g (1.09mol) AA were added to a four-necked flask containing 2000mL deoxygenated DMSO, and mechanical stirring was started until completely dissolved; 0.04g AIBN was weighed and added to the reaction system, and the reaction was carried out at 80°C for 18h under a nitrogen environment; after the reaction was stopped, the reaction system was naturally cooled to room temperature, 125.6g (1.09mol) NHS and 112.6g (0.545mol) DCC were weighed and dissolved in 225mL DMF and added to the reaction system, and magnetic stirring was carried out at 25°C for 96h; after the reaction was completed, the reaction byproduct DCU was removed by suction filtration, and the solution was mixed with 2000mL isopropanol, and then precipitated in 13000ml ether and filtered to obtain a solid product. The solid product was washed three times with 2500mL ether and dried at 40°C under reduced pressure to obtain P (NVP-co-AA-co-AA (NHS)).

[0107] Application Example 1

[0108] A tissue patch comprises a tissue adhesion layer and an anti-tissue adhesion layer which are superimposed on each other; wherein the tissue adhesion layer is the copolymer prepared in Example 1, and the anti-tissue adhesion layer is PLGA.

[0109] The preparation method is as follows:

[0110] (1) Prepare the following two solutions A and B:

[0111] Solution A: The anti-tissue adhesion layer material (PLGA) was dissolved in DCM to prepare a solution with a mass fraction of 7.5%;

[0112] Solution B: 10 g of tissue adhesion layer material (copolymer prepared in Example 1) was dissolved in 100 mL of DCM / MeOH=1:2 (v / v) to prepare a solution with a mass fraction of 10%.

[0113] (2) Casting solutions A and B onto release paper with silicone on the back:

[0114] Layer 1: 10 mL of solution A was cast on release paper and dried at room temperature / atmospheric pressure for 30 minutes;

[0115] Layer 2: 5 mL of solution B was cast on layer 1 and dried at room temperature / atmospheric pressure for 4 hours;

[0116] Layer 3: 5 mL of solution A was cast onto layer 2 and dried at room temperature / atmospheric pressure for 30 minutes;

[0117] Layer 4: 15 mL of solution B was cast onto layer 3 and dried at room temperature / atmospheric pressure for 8 hours;

[0118] After drying, the patch was peeled off from the release paper and cut into the desired shape to obtain a tissue patch (thickness 60±20 μm).

[0119] The adhesion mechanism of tissue film is shown in the figure Figure 2 shown.

[0120] Application Example 2-5

[0121] Application Examples 2-5 respectively provide a tissue patch, which differs from Application Example 1 only in that the tissue adhesion layer in Application Example 1 is replaced by the copolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS)) provided in Example 2, the copolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS)) provided in Example 3, the copolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS)) provided in Example 4, and the copolymer P(NVP-co-PEGDA-co-IA-co-IA(NHS)) provided in Example 5, respectively. The rest refers to Application Example 1.

[0122] Comparative application example 1

[0123] Comparative Application Example 1 provides a tissue patch, which differs from Application Example 1 only in that the tissue adhesion layer in Application Example 1 is replaced by the copolymer P(NVP-co-AA-co-AA(NHS)) provided in Comparative Example 1, and the rest is for reference to Application Example 1.

[0124] Test Case

[0125] Test method:

[0126] (1) Adhesion performance: According to the ASTM F2255 test standard, the tissue film was cut into 1 cm × 2.5 cm size for later use, and the anti-adhesion layer was fixed on a 2.5 cm × 6 cm silicone sheet with isocyanate glue; the pig skin was processed according to the standard and cut into 2.5 cm × 6 cm size, and was in stable contact with the tissue film with a contact area of ​​1 cm × 2.5 cm, and was squeezed with a force of 2 N for 60 s; the electronic universal testing machine was started to gradually separate the tissue film from the pig skin, and the maximum force when pulling apart was recorded to measure the adhesion strength.

[0127] (2) Mechanical strength: The bursting pressure was measured by recording the maximum value displayed on the pressure gauge when the tissue film was damaged under the action of the water pressure continuously increased by the peristaltic pump through the bursting pressure test method.

[0128] (3) Degradation performance: According to the test standard YY / T 0473-2004, a simple in vitro degradation test was designed. The tissue film was immersed in PBS pH 7.4 at 37°C, and the change in sample weight was tested every day. The maximum swelling multiple within 168 hours was recorded.

[0129] Swelling ratio = (remaining mass / initial mass) × 100%.

[0130] The results are summarized in Table 1. The in vitro degradation test results of the tissue patch provided in Application Example 2 and Comparative Application Example 1 are shown in Table 1. Figure 3 shown.

[0131] Table 1

[0132] Grouping Adhesion strength (kPa) Explosion pressure(kPa) Maximum swelling ratio Application Example 1 16 25 4 Application Example 2 20 40 7 Application Example 3 25 45 6 Application Example 4 30 49 6 Application Example 5 32 50 10 Comparative application example 1 10 20 32

[0133] The test results show that the present invention adopts itaconic acid as a reaction monomer and fully utilizes the active carboxyl group in itaconic acid to meet high adhesion. The adhesion strength, mechanical strength and degradation time of the tissue film further prepared by the obtained tissue adhesion material are controllable, and the swelling property is low, which reduces the risk of falling off during service. Specifically, the adhesion strength is 16-32kPa, the bursting pressure is 25-50kPa, and the swelling multiple is less than 10 within 168h.

[0134] When the comparative application example 1 is replaced with an acrylic structural unit, the obtained film has weak adhesion, poor strength, and high water absorption, and cannot meet the application requirements.

[0135] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A tissue adhesion material, characterized in that: The tissue adhesion material includes a linear or branched ternary or higher multi-polymer, and the raw materials for preparing the multi-polymer include itaconic acid, a tissue adhesion compound, a film-forming compound, an initiator and a promoter.

2. The tissue adhesion material according to claim 1, characterized in that: The tissue adhesive compound includes any one or a combination of at least two of imidate, N-hydroxysuccinimide, acrylate, maleimide, glutaraldehyde, catechol, epoxide, isocyanate or vinyl compound; Preferably, the molar ratio of itaconic acid to the tissue adhesive compound is 5:1-1:

5.

3. The tissue adhesion material according to claim 1 or 2, characterized in that: The film-forming compound includes any one or a combination of at least two of N-vinyl pyrrolidone, styrene, methyl methacrylate or butyl acrylate; Preferably, the molar ratio of itaconic acid to the film-forming compound is 5:1-1:

5.

4. The tissue adhesion material according to any one of claims 1 to 3, characterized in that: The initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, persulfate or dibenzoyl peroxide, or a combination of at least two thereof; Preferably, the accelerator comprises any one or a combination of at least two of N,N-dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; Preferably, the raw materials for preparing the multi-polymer further include a cross-linking agent; Preferably, the cross-linking agent includes any one or a combination of at least two of polyethylene glycol diacrylate, polypropylene glycol diacrylate, polycaprolactone, polyurethane or polyacrylamide; Preferably, the molar ratio of itaconic acid to the cross-linking agent is 1:1-50:

1.

5. A method for preparing a tissue adhesion material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing an itaconic acid monomer, an initiator and a solvent, and subjecting the mixture to a free radical polymerization reaction initiated by heat to obtain a solution A; (2) mixing solution A, a film-forming compound and an initiator, and subjecting the mixture to a free radical polymerization reaction initiated by heat to obtain solution B; (3) Solution B, the tissue adhesion compound and the accelerator are mixed and subjected to an esterification reaction to obtain the tissue adhesion material.

6. The preparation method according to claim 5, characterized in that: The amount of the initiator in step (1) is 0.2-5% of the total mass of itaconic acid and the cross-linking agent; Preferably, the solvent in step (1) comprises any one or a combination of at least two of dimethyl sulfoxide, deoxytoluene, N,N-dimethylformamide, 1,4-dioxane or N,N-dimethylacetamide; Preferably, the amount of the solvent used in step (1) is 2-10 times the total mass of itaconic acid and the cross-linking agent; Preferably, the temperature of the free radical polymerization reaction in step (1) is 40-80° C., and the time of the free radical polymerization reaction is 1-24 h; Preferably, step (1) further comprises adding a cross-linking agent and mixing it with the itaconic acid monomer, the initiator and the solvent; Preferably, the amount of the initiator in step (2) is 0.2-2% of the mass of the film-forming compound; Preferably, the temperature of the free radical polymerization reaction in step (2) is 40-80° C., and the time of the free radical polymerization reaction is 1-24 h.

7. The preparation method according to claim 5 or 6, characterized in that: In step (3), the molar ratio of the tissue adhesion compound to the promoter is 1:0.5-1:2; Preferably, the temperature of the esterification reaction in step (3) is 20-30° C., and the time of the esterification reaction is 24-96 hours; Preferably, the esterification reaction in step (3) further includes a post-treatment step; Preferably, the post-treatment comprises filtering the system after the esterification reaction, adding a precipitant to the filtrate for precipitation, then redissolving the precipitate, and adding the precipitant again for precipitation; then washing the precipitate with a detergent to obtain the tissue adhesion material; Preferably, the precipitant comprises any one of ethanol, isopropanol, n-propanol, ether or ethyl acetate, or a combination of at least two thereof; Preferably, the solvent used for the re-dissolution includes any one of dichloromethane, chloroform or methanol, or a combination of at least two thereof; Preferably, the detergent comprises any one of ether, n-hexane, petroleum ether, ethyl acetate, butyl benzoate, carbon tetrachloride, propyl ether or n-pentane, or a combination of at least two thereof.

8. Use of the tissue adhesion material according to any one of claims 1 to 4 in the preparation of a hemostatic agent, a tissue sealant, a wound adhesive or a drug carrier.

9. A tissue patch, characterized in that: The tissue patch includes a stacked tissue adhesion layer and an anti-tissue adhesion layer; The tissue adhesion layer comprises the tissue adhesion material according to any one of claims 1-4.

10. The tissue patch according to claim 9, characterized in that: The anti-tissue adhesion layer comprises any one of polylactic acid, polyglycolic acid, polycaprolactone, polyhydroxyalkanoate or lactic acid-glycolic acid copolymer or a combination of at least two thereof; Preferably, the thickness of the tissue patch is 0.01-1 mm.